HIV prevention and public health issues: a global perspective - Vermund, Sten H. (Henry Stewart Talks, 2007)
Global HIV situation, Modes of transmission, Quantitative rationale for prevention, Varying strategies for prevention, Implementation and expansion of known effective prevention approaches
Updated at 2018/01/31